TI_GERICHTE 16.2016.51 vom 15. Januar 2019 , Responsabilità del proprietario dei un'opera - segnaletica stradale - TI Tribunale d'appello (2019)
Responsabilità del proprietario dei un'opera - segnaletica stradale